TEACHING STRATEGIES FOR USING WITH PERSONAL LEARNING ENVIRONMENTS - Serra, Luisa; Martínez, Marle; Díaz, Alfredo (Revista Arbitrada Formación Gerencial, 2022)
Teaching strategies are related to all activities used to improve the learning climate in personal learning environments. Teachers play the role of a model for students, a counselor for life in reality and on the web, a set of entities or elements that guide learning. The study of teaching strategies in personal learning environments (PLE) can emphasize the importance of using media libraries, places to write, comment, analyze, recreate, evaluate, recommend and publish. It also distinguishes the differences between being a normal teacher or autonomous, creative one, out of traditional schemes and paradigms that are often an uncomfortable straitjacket for new generations. This research was conducted under the positivist paradigm, classified as projective with descriptive level and a non-experimental-transversal design. In order to collect data, a validated instrument was used, and the information was analyzed with descriptive statistics. The results showed that in personal learning environments, teachers must guide, plan, promote and motivate student participation achieving significant and collaborative learning. Therefore, methodological and theoretical guidelines were created for a personal learning environment to optimize the development of skills in educational computing course from Computing Education Career, from University of Zulia.